2021
DOI: 10.1007/s40290-021-00399-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Quality in Cancer Research: Strategy to Assess Data Integrity of Germline Variants Inferred from Tumor-Only Testing Sequencing Data

Abstract: In the majority of cancers, pathogenic variants are only found at the level of the tumor; however, an unusual number of cancers and/or diagnoses at an early age in a single family may suggest a genetic predisposition. Predisposition plays a major role in about 5 to 10% of adult cancers and in certain childhood tumors. As access to genomic testing for cancer patients continues to expand, the identi cation of Potential Germline Pathogenic Variants (PGPV) through tumor-DNA sequencing is also increasing. Statistic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 25 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…We provided several examples in our previous study on how these checks can be designed. 2 The authors suggested that integration of clinical, familial and ancestry information may improve the probability of PGV identification. 1 This could be achieved by leveraging clinicogenomic databases, which contain longitudinal data (eg, histology and laboratory data) of patients who undergo tumor genomic testing.…”
Section: To the Editormentioning
confidence: 99%
See 4 more Smart Citations
“…We provided several examples in our previous study on how these checks can be designed. 2 The authors suggested that integration of clinical, familial and ancestry information may improve the probability of PGV identification. 1 This could be achieved by leveraging clinicogenomic databases, which contain longitudinal data (eg, histology and laboratory data) of patients who undergo tumor genomic testing.…”
Section: To the Editormentioning
confidence: 99%
“…1 This could be achieved by leveraging clinicogenomic databases, which contain longitudinal data (eg, histology and laboratory data) of patients who undergo tumor genomic testing. 2 A last suggestion for an efficient quality check would be to cross-check inferred PGV against the Cancer Genes Census (CGC) list provided in the Catalogue of Somatic Mutations In Cancer. 7 Cancer genes are provided in a table and can be filtered for germline—it should be easy to build in the pipeline an automated check against the CGC table, to discard potential false-positive PGVs.…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations